Atividade de estudo e autonomia no processo de produção da pesquisa - Rossetto, Gislaine Aparecida Rodrigues da Silva (2013)
It is understood that we may contribute to the construction of autonomy in research production from various challenging experiences that an individual may go through to while in the academy, especially in the stricto sensu Post-Graduation in Education. Thus, it interested us to investigate the production of study activity as a trigger for the autonomy in research in the elaboration of master‟s dissertations and doctoral theses. The specific aims were to identify the steps to the development of the study activity in the elaboration of dissertations and theses; to acknowledge the actions and operations that are implied in this process of research production; and to analyze the actions and operations directly connected to the process of construction of autonomy for the researcher. The methodological approach used was of a qualitative nature and was developed from the sociocultural narrative approach. The subjects of this study were two master‟s students and three doctoral students who participate in the Group of Research and Teacher Formation: Basic and Higher Education (Grupo de Pesquisa e Formação de Professores: Ensino Básico e Superior GPFOPE). This research group is part of the stricto sensu Post-Graduation Program in Education of the Federal University of Santa Maria. The theoretical basis of the study is Vygotsky (1993; 1994; 1995; 1997; 2007; 2010a; 2010b), Leonitiev (1978; 1984), Davidov (1987), Davidov and Márkova (1987a; 1987b), Marx (2011) and Kozulin (2002) for the concept of activity and study activity; Kant (1783), Hegel (2010), Schneewind (2009), Castoriadis (1991), Rouanet (n.d.), Rué (2009), Monereo and Pozo (n.d.), Martin (n.d.), Vygotsky (1997; 2010) and Davidov and Márkova (1987a; 1987b) for the concept of autonomy. With the results found we were able to infer that this study allowed us to highlight the possibility of understanding what the process of research production and autonomy construction in the development of dissertations and theses is, being research activity the main guide. Two categories emerged from the analysis of the narratives provided by the participants: research production and research autonomy. The participants in general manifested that autonomy construction is a particular although not lonely process, once it is necessary to have the presence of the other for this sort of learning. Being an autonomous subject means being authentic and not a mere reproducer of the other. Three tensions resulted from the process of autonomy construction in research through experiencing: the research activity: personal, professional and investigative field needs; research path and autonomy construction, time of personal learning and time employed in research. This peculiarity must be understood as an authorial feature in the process of learning the research. Therefore, the particular ways through which research is produced lead the individual to gradually build their autonomy.